Analogi og genealogi: protestantiske reformbuddhismer - Borup, Jørn (Religionsvidenskabeligt Tidsskrift, 2018)
ENGLISH ABSTRACT: Buddhism's history can be seen as a succession of reformisms. To focus the relevance of the concept, it is understood in this article as a concept measuring significant change within the religion itself and the surrounding community. With three examples from different contexts: ‘Protestant Buddhism' in the 19th century Sri Lanka, the Shin Buddhist reform movement in the Japanese Middle Ages, and Japanese diaspora Buddhism in Hawaii, the relevance of the term is investigated in relation to both genealogical and analogical reference to the Christian Protestant Reformation. DANSK RESUME: Buddhismens historie kan ses som en lang række af reformismer. For at afgrænse begrebets relevans anvendes det i denne artikel om markante forandringstiltag med betydning for religionen selv og det omkringliggende samfund. Med tre eksempler fra forskellige kontekster: ‘Protestantisk buddhisme' i det 19. årh-. på Sri Lanka, shin-buddhistisk reformbevægelse i den japanske middelalder samt japansk diasporabuddhisme i Hawaii, undersøges begrebets relevans med genealogisk og analogisk reference til den kristne, protestantiske reformation.